SIGNIFICANCE OF THIOL-DISULPHIDE BALANCE IN SARS - CoV-2 INFECTION - Simic, Prof. Tatjana (Medicinski podmladak, 2021)
Studies of the molecular mechanisms regarding interaction of different viruses with receptors on the host cell surface have shown that the viral entry depends on the specific relationship between free thiol (SH) groups and disulfides on the virus surface, as well as the thiol disulfide balance on the host cell surface. The presence of oxidizing compounds or alkylating agents, which disturb the thiol-disulfide balance on the surface of the virus, can also affect its infectious potential. Disturbed thiol-disulfide balance may also influence protein-protein interactions between SARS-Cov-2 protein S and ACE2 receptors of the host cell. This review presents the basic mechanisms of maintaining intracellular and extracellular thiol disulfide balance and previous experimental and clinical evidence in favor of impaired balance in SARS-Cov-2 infection. Besides, the results of the clinical application or experimental analysis of compounds that induce changes in the thiol disulfide balance towards reduction of disulfide bridges in proteins of interest in COVID-19 infection are presented.